ESTIMATE OF MASS LOSS RATE FROM ALGOL - TYPE SYSTEMS BASED ON RADIOFLUXES - Glazunova, L. V.; Pustylnik, I. B. (Одеські астрономічні публікації, 2017)
The estimates of the upper limit mass loss rate from Algol-type binaries based on observations at radio wavelengths match well the results obtained from the optical data. This mass loss rate suggests that Algol-type systems observed at radio wave lengths have optically thick core, the sizes of the latter are larger than the size of the system. Due to this fact all the Algol-type binaries are weak single radio sources.